Evaluation of the effects of Corchorus olitorius L. and Carapa procera in the treatment of obesity - Adon, Arsène M.; Ackah, Bognan A. A. J.; Yayé, Guillaume Y.; Okou, Constantin O.; Brahima, Raoul K. K.; Djaman, Joseph A. (International Journal of Research in Medical Sciences, 2018)
Background: The obesity remains a pathology today which expands. It leads in its wake much pathology with very serious consequences. It is therefore necessary to take steps to curb this nutritional pathology. Thus, two plant species including Carapa procera and Corchorus olitorius have been tested to assess their effect on this pathology. Methods: Aqueous extracts of Carapa procera bark and Corchorus olitorius roots were tested on rats and biochemical parameters were evaluated. Besides, a chemical characterization was led. Results: These plant extracts contain bioactive molecules that have a regressive activity on the plasma levels of cholesterol, triglyceride and LDL-cholesterol. These bioactive molecules increase the level of HDL-cholesterol. These 2 species are non-toxic on renal, hepatic and pancreatic functions in view of the values of urea, creatinine and blood glucose. Conclusions: Of these 2 extracts, the aqueous extract of Corchorus olitorius is more active.